The Effect of Strengthening Exercise to Improve Angle Trunk Rotation in Patient with Scoliosis (Lembaga Penerbitan Universitas Esa Unggul, 2022)
Background: Scoliosis is a three-dimensional spinal deformity in the form of lateral curvature and rotation accompanied by compensation, which is characterized by asymmetry in shoulder height, waist line, and the distance between the elbows to the pelvis as well as vertebral rotation, and rib hump which triggers the patient to experience pain, decreased muscle strength, limited movement so that the patient has difficulty lifting and lowering objects, standing and sitting for too long. Purpose: The study aimed to determine the effect of strengthening exercise to improve angle trunk rotation in patient with scoliosis. Methods: The research method used is in the form of a case study with 1 patient given physiotherapy intervention and evaluation 4 times. To overcome the problems that occur in this study are used strengthening exercises to determine the effect of strengthening exercise on changes in the angle of trunk rotation in cases of scoliosis. Strengthening exercise is one of the physiotherapy interventions the authors use to activate muscles so that they can reduce pain, increase muscle strength, and improve postural control so that patients are able to move optimally as measured by objective parameters in the form of a scoliometer. Results: The results showed that there was a decrease in the degree of vertebral curvature in scoliosis cases after four evaluations, as evidenced by the first evaluation with a scoliosis degree of 6° and in the IV evaluation the score became 2.5°. Conclusion: Based on these results, it can be concluded that strengthening exercise has been shown to provide improvement in reducing the angle of trunk rotation in cases of scoliosis.